Implementation of Pancasila Moral Education towards Character Building Students at SMP Negeri 5 Depok - Zakiah, Vebi Febrianti (Jurnal Civicus, 2024)
The This research discusses how the implementation process of Pancasila moral education runs at SMP Negeri 5 Depok School. This research is a qualitative study with a descriptive design explored through eleven key informants consisting of students, school staff, and parents of students. The field findings illustrate that the provision of Pancasila moral education has a positive impact on student character building. The supporting factors are the bond between teachers, the availability of free resources around the school, and the sincerity of parents. The inhibiting factors faced are the lack of experience of teachers related to understanding Pancasila moral education, the absence of a detailed curriculum, the attitude of parents who are less cooperative, and the influence of students' unsupportive home environment.